Detection of small-size solder ball defects through heat conduction analysis - Zhou, Xiuyun; Chen, Yaqiu; Lu, Xiaochuan (Review of scientific instruments, 2018)
Aiming to solve the defect detection problem of a small-size solder ball in the high density chip, heat conduction analysis based on eddy current pulsed thermography is put forward to differentiate various defects. With establishing the 3D finite element model about induction heating, defects such as cracks and void can be distinguished by temperature difference resulting from heat conduction. Furthermore, the experiment of 0.4 mm-diameter solder balls with different defects is carried out to prove that crack and void solder can be distinguished. Three kinds of crack length on a gull-wing pin are selected, including 0.24 mm, 1.2 mm, and 2.16 mm, to verify that the small defect can be discriminated. Both the simulation study and experiment result show that the heat conduction analysis method is reliable and convenient.